Hypoglossal nerve stimulation for obstructive sleep apnea: A review of the literature - Christina M. Wray (KeAi Communications Co., Ltd., 2016)
Objective: To review the indications and clinical evidence supporting hypoglossal nerve stimulation (HNS) therapy for the treatment of moderate-to-severe obstructive sleep apnea (OSA). Methods: Peer reviewed literature on hypoglossal nerve stimulation therapy for obstructive sleep apnea from 2001 to 2016. Results: The only currently FDA-approved HNS device for the treatment of moderate-to-severe OSA is produced by Inspire Medical Systems, which recently published its 36-month outcomes data from its Stimulation Therapy for Apnea Reduction (STAR) trial. HNS therapy is currently indicated for moderate-to-severe OSA patients who are CPAP-intolerant, have a body mass index <32, apnea-hypopnea index <50, and without a concentric pattern of upper airway collapse on sleep endoscopy. Conclusions: Data from the STAR trial suggests that a subset of OSA patients can achieve a significant therapeutic response from hypoglossal nerve stimulation. However, these results may be limited in their generalizability to the broader OSA population. Keywords: Hypoglossal nerve stimulation, Obstructive sleep apnea, Upper airway stimulation, CPAP-intolerant, Neurostimulation